DEVELOPING READING MATERIALS OF DESCRIPTIVE TEXT BASED ON SCIENTIFIC APPROACH FOR TENTH GRADE STUDENTS OF COMPUTER NETWORK ENGINEERING AT SMK MULTI KARYA MEDAN - SUSANTRI LECESTER; Elia Masa Gintings (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This study deals with the reading materials development for the first grade students at SMK Multi Karya Medan. The research conducted by Research and Development (R & D). It was developed through six stages; 1) Gathering the data & information, 2) Analyzing the data, 3) Designing a new reading materials, 4) Validating by experts, 5) Revising a new reading materials and 6) Final product. It was conducted at SMK Multi Karya Medan, the subject of this research was X grade students of Computer Network Engineering Study Program. The objectives of this study are to investigate the students’ need and to develop the appropriate reading materials for the students. The data were gathered by administering interview to English teacher and distributing questionnaire to 25 students. The interview and questionnaire results prove that the students need English reading materials which is contained the appropriate knowledge or topic with the Computer Network Engineering study program, syllabus and students’ level. The developed materials are descriptive text. The three topics of descriptive text have been developed, the topics are about Bill Gates, Computer History Museum, and Sillicone Valley. The development of reading materials in descriptive texts are based on Hutchinson and Waters theory through 4 stages, such as; defining objectives, creating the framework, designing the model of reading materials and refining the model of reading materials. The new reading materials are validated by two experts, they are English lecturer and and English teacher. The average scores of validation are 4.3 from English lecturer and 4.2 from English teacher. It can be concluded that the developing materials categorized as relevant or appropriate for tenth grade students of Computer Network Engineering Program.